2008
DOI: 10.1111/j.1745-9125.2008.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Stability of Co‐offending and Co‐offenders Among a Sample of Youthful Offenders*

Abstract: Scholars have long argued that delinquency is a group phenomenon. Even so, minimal research exists on the nature, structure, and process of co‐offending. This investigation focuses on a particular void, namely the stability of 1) co‐offending and 2) co‐offender selection over time, for which divergent theoretical expectations currently exist that bear on issues central to general and developmental/life‐course theories of crime. By relying on individual‐level, longitudinal data for a sample of juvenile offender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 61 publications
(76 reference statements)
3
92
0
1
Order By: Relevance
“…Reiss [13] concludes that the majority of co-offending groups are unstable, and their relationships are short-lived. This is corroborated by McGloin et al, [15] who showed that there is some stability in co-offending relationships over time for frequent offenders, but in general, delinquents do not tend to reuse co-offenders. Reiss et al [14] also found that cooffenders have many different partners, and are unlikely to commit crimes with the same individuals over time.…”
Section: Related Worksupporting
confidence: 53%
See 1 more Smart Citation
“…Reiss [13] concludes that the majority of co-offending groups are unstable, and their relationships are short-lived. This is corroborated by McGloin et al, [15] who showed that there is some stability in co-offending relationships over time for frequent offenders, but in general, delinquents do not tend to reuse co-offenders. Reiss et al [14] also found that cooffenders have many different partners, and are unlikely to commit crimes with the same individuals over time.…”
Section: Related Worksupporting
confidence: 53%
“…However, Reiss [13] also states that high frequency offenders are "active recruiters to delinquent groups and can be important targets for law enforcement." It should be noted that the findings of these works were obtained on very small datasets: 205 individuals in [14], and 5600 individuals in [15], and may therefore not be representative.…”
Section: Related Workmentioning
confidence: 96%
“…The minimal research on co-offending patterns in criminal careers shows that it exhibits a strikingly similar profile to the aggregate age-crime curve van Mastrigt and Farrington 2009), that there are distinct trajectories of co-offending over the course of the juvenile criminal career and that juvenile delinquents generally tend not to ''re-use'' co-offenders, though frequent offenders show a greater propensity to do so (McGloin et al 2008), that higher levels of co-offender network redundancy (more dense networks) are related to higher levels of specialized offending in group crimes, but no such relationship exists with overall (i.e., solo and group) offending diversity (McGloin and Piquero 2009), and that the presence of more co-offenders (i.e., larger groups) will be related to an increased likelihood of violent crime (McGloin and Piquero 2010). However, these studies emerge from two select data sources (the Cambridge data of South London males and a sample of juvenile offenders followed to age 17); thus, there is an important need to examine cooffending patterns in other data sources, across distinct offense types, and throughout the entire life-course.…”
Section: Policy Issuesmentioning
confidence: 99%
“…Community mining has many related properties to the graph-cut problem. In general social network analysis and community mining can be seen under graph mining [25]. The sub-graph identification is very useful in community mining.…”
Section: Community Miningmentioning
confidence: 99%